The musical environment and auditory plasticity: hearing the pitch of percussion - Mclachlan, Neil M.; Marco, David J.; Wilson, Sarah J. (Frontiers in Psychology, 2013)
Although musical skills clearly improve with training, pitch processing has generally been believed to be biologically determined by the behavior of brain stem neural mechanisms. Two main classes of pitch models have emerged over the last 50 years. Harmonic template models have been used to explain cross-channel integration of frequency information, and waveform periodicity models have been used to explain pitch discrimination that is much finer than the resolution of the auditory nerve. It has been proposed that harmonic templates are learnt from repeated exposure to voice, and so it may also be possible to learn inharmonic templates from repeated exposure to inharmonic music instruments. This study investigated whether pitch-matching accuracy for inharmonic percussion instruments was better in people who have trained on these instruments and could reliably recognize their timbre. We found that adults who had trained with Indonesian gamelan instruments were better at recognizing and pitch-matching gamelan instruments than people with similar levels of music training, but no prior exposure to these instruments. These findings suggest that gamelan musicians were able to use inharmonic templates to support accurate pitch processing for these instruments. We suggest that recognition mechanisms based on spectrotemporal patterns of afferent auditory excitation in the early stages of pitch processing allow rapid priming of the lowest frequency partial of inharmonic timbres, explaining how music training can adapt pitch processing to different musical genres and instruments.